Taking Cantonal Variations of Integration Policy Seriously — or How to Validate International Concepts at the Subnational Comparative Level - Manatschal, Anita (My University, 2011)
Subnational varieties of immigrant integration policy, which are particularly salient in federal states, remain largely neglected by migration studies. Following Lijphart, who long demanded to verify international research at the subnational level, this study aims at capturing subnational policy variations using the example of Swiss cantons. In line with international approaches, cantonal integration policies are conceptualized and measured in terms of immigrants’ ease or difficulty of access to civic, political, socio‐structural, as well as cultural and religious rights and obligations. The transfer of an international concept to the subnational level facilitates a validation of the former, which constitutes a second neglected research field. Finally, a look at the empirical evidence allows testing the construct validity of our measurement: in line with theoretical assumptions, our data reveal a clear linguistic divide, an institutionalised “Röschtigraben”, with German speaking cantons exhibiting overall more restrictive policies than Latin cantons.
Keywords: Integration Policy; Citizenship; Subnational Comparison; Swiss Cantons